Ontological and intercultural anthropology of health among the shuar peoples of Zamora-Chinchipe - Christian Tym (Íconos)
This article shows the connections between Anglophone anthropology and the political philosophy of interculturality, to which little attention has been given in Latin America. Specifically, the contributions of the so-called ‘ontological turn’ are detailed in order to develop a theory of interculturality that addresses the differences between Indigenous peoples and Western societies. It is argued that the concept of “culture” constitutes an “ambivalence”, and that from this turn and its critics one can understand better interculturality as a positive proposal from Indigenous intellectuals. The debates on the representation of difference that followed the ontological turn point toward the importance of intracultural diversity; therefore, it is crucial to develop nuanced representations of Indigenous and Western cultures, considering different characteristics that distinguish the communities and individuals of each group. This argument is developed based on intercultural health through the case study of health practices and preferences in the shuar population of the Ecuadorian province of Zamora-Chinchipe. It is concluded that an interculturality is required that does not mean the ethnicization of public policies, but rather their localization and adaptation to the preferences of people in every distinct zone within national territories.